2009
DOI: 10.3233/jad-2009-1015
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic Shifts in Circulating CD4 but not CD8 T Cell Subsets in Mild Alzheimer's Disease

Abstract: The distribution of peripheral T cell subsets in young and healthy old people is markedly different, characterized by decreased numbers of naïve cells and increased numbers and clonal expansions of memory cells, predominantly in the CD8+ MHC class I-restricted subset. Here, however, we document dramatic alterations in naïve and memory subsets of CD4+ cells in patients with mild Alzheimer's disease (AD), with greatly decreased percentages of naïve cells, elevated memory cells, and increased proportions of CD4+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
164
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 180 publications
(185 citation statements)
references
References 35 publications
19
164
2
Order By: Relevance
“…Alternatively the shift from naïve to late memory CD4+ cells in AD patients can be the result of the capture of Aβ by local APC in the brain and the migration of these cells towards secondary lymph nodes inducing T cell stimulation, as suggested by Monsonego et al (Monsonego et al, 2003). The present results are consistent with our previous report of a pilot study of mild AD patients (Larbi et al, 2009), but extend that study beyond the diagnosis of mild AD to include moderate AD. Moreover, the employment of a different set of markers to define naïve and differentiated memory cells in these two studies in patients from two different countries, nonetheless with consistent results, suggests that these findings are likely to be robust.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Alternatively the shift from naïve to late memory CD4+ cells in AD patients can be the result of the capture of Aβ by local APC in the brain and the migration of these cells towards secondary lymph nodes inducing T cell stimulation, as suggested by Monsonego et al (Monsonego et al, 2003). The present results are consistent with our previous report of a pilot study of mild AD patients (Larbi et al, 2009), but extend that study beyond the diagnosis of mild AD to include moderate AD. Moreover, the employment of a different set of markers to define naïve and differentiated memory cells in these two studies in patients from two different countries, nonetheless with consistent results, suggests that these findings are likely to be robust.…”
Section: Discussionsupporting
confidence: 92%
“…These data are not in complete agreement with other reports of no differences in the percentage and absolute number of CD3+ T cells, NK cells or CD4+ and CD8+ T cells (Speciale et al, 2007). In our own pilot study we showed that major changes are seen within the CD4+ T cell subset in mild AD patients compared to healthy elderly controls (Larbi et al, 2009) whereas the more marked changes in the CD8 subsets were seen equally in both patients and age-matched controls. To confirm and extend our previous findings in a different population (Italian not Canadian), here we tested a larger group of AD patients (n = 40, one group of mild and one group of moderate AD) compared to healthy old (n = 21) and young subjects (n = 11) using multiparameter flow cytometry, including new markers to better characterize the immunological profile of these patients.…”
Section: Discussioncontrasting
confidence: 84%
See 3 more Smart Citations